2001
DOI: 10.1143/jjap.40.l638
|View full text |Cite
|
Sign up to set email alerts
|

Nonlinear Photoluminescence Behavior in Closely Packed CdSe Nanocrystal Thin Films

Abstract: We report on the cooperative photoluminescence (PL) properties of closely packed CdSe nanocrystal thin films and propose a model to elucidate the nonlinear PL behavior. The PL exhibits an initial decay and a subsequent enhancement under continuous excitation, which are attributed to the photodarkening and the effects of photooxidation (neutralization and suppression of the photoionization rate). The PL enhancement correlates with the degree of oxidation. X-ray photoelectron spectroscopy (XPS) confirms that pho… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
58
0

Year Published

2008
2008
2018
2018

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 37 publications
(59 citation statements)
references
References 17 publications
1
58
0
Order By: Relevance
“…1 2 3 4 5 6 7 8 9 10 11 12 13 14 15 16 17 18 19 20 21 22 23 24 25 26 27 28 29 30 31 32 33 34 35 36 37 38 39 40 41 42 43 44 45 46 47 48 49 50 51 52 53 54 55 56 57 58 59 attributed to the binding of the surface ligand TOPO to cadmium but not selenium. There is apparently no evidence of cadmium oxidizing in TOPO-covered QDs exposed to air, [1][2][3] but there is when it is capped by pyridine. 2,3 Katari et al 3 found that the oxidized selenium subsequently desorbs.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…1 2 3 4 5 6 7 8 9 10 11 12 13 14 15 16 17 18 19 20 21 22 23 24 25 26 27 28 29 30 31 32 33 34 35 36 37 38 39 40 41 42 43 44 45 46 47 48 49 50 51 52 53 54 55 56 57 58 59 attributed to the binding of the surface ligand TOPO to cadmium but not selenium. There is apparently no evidence of cadmium oxidizing in TOPO-covered QDs exposed to air, [1][2][3] but there is when it is capped by pyridine. 2,3 Katari et al 3 found that the oxidized selenium subsequently desorbs.…”
Section: Resultsmentioning
confidence: 99%
“…[1][2][3][4][5][6] This leads to a decrease in the diameter of the core, which is accompanied by a decrease in the wavelength of absorption and luminescence and often a decrease in photoluminescence (PL) intensity. This product oxide shell also serves as a barrier to the transport of charge, including electrons, holes, and excitons.…”
mentioning
confidence: 99%
“…One change is augmentation of their emission efficiencies through photoinduced fluorescence enhancement (PFE). [6][7][8][9][10][11] The process of PFE has been investigated under different conditions, including gaseous environments, 11,12 substrates, 13 and light intensities or wavelengths. 14 The origin of the phenomenon has been attributed to mechanisms that include photoadsorption of water molecules, 4,15 photoannealing, 16 stabilization with surfactant molecules or surface ligand passivation, 17,18 and photoionization of QDs and ejection of electrons (photoelectrification).…”
Section: Introductionmentioning
confidence: 99%
“…14 The origin of the phenomenon has been attributed to mechanisms that include photoadsorption of water molecules, 4,15 photoannealing, 16 stabilization with surfactant molecules or surface ligand passivation, 17,18 and photoionization of QDs and ejection of electrons (photoelectrification). [6][7][8][9] Irradiation of colloidal QDs with light can also lead to their oxidation. Characteristic signatures of such oxidation are a blueshift and broadening of the fluorescence spectra.…”
Section: Introductionmentioning
confidence: 99%
“…It is known that the emission spectrum of nanocrystals exhibits a Gaussian like emission line shape on a wavelength scale. This kind of Gaussian fit is also used in several references [27][28][29]. Using Gaussian fits to the steady-state luminescence of the mixed nanocrystal solids and weighting only according to the emission levels of small and large dots alone, without considering energy transfer, we calculate the expected QE of the mixed solids to be only 25.7%.…”
mentioning
confidence: 99%